Ceragenins Prevent the Development of Murine Vaginal Infection Caused by Gardnerella vaginalis - Urszula Wnorowska; Ewelina Piktel; Tamara Daniluk; Paulina Paprocka; Paul B. Savage; Bonita Durnaś; Robert Bucki (MDPI AG, 2024)
Background/Objectives: Bacterial vaginosis (BV), an infection caused primarily by Gardnerella vaginalis, is the most prevalent vaginal infection. Although BV is often characterized by an asymptomatic course, it can lead to considerable health complications. Currently, BV therapy choices are limited, and available treatments are complicated by concerns about antibiotic resistance. Ceragenins, which together comprise an innovative class of low molecular-weight, cholic acid-based antibacterial agents, have emerged as potential alternatives to conventional treatments. Methods: This study investigates (i) the antibacterial activity of ceragenins against G. vaginalis in in vitro experimental settings at varied pH, and (ii) the effectiveness and anti-inflammatory properties of CSA-13 in a G. vaginalis-induced bacterial vaginosis animal model. Results and Conclusions: We demonstrate that ceragenins, particularly CSA-13, maintain their antibacterial efficacy throughout pH range of 4.5-7, with the highest activity observed at neutral pH (7.0). Additionally, in an animal model, beneficial effects of ceragenins are attributed to anti-inflammatory properties of these compounds, making these compounds promising agents as potential new treatment options against G. vaginalis-associated vaginal infections.